2004
DOI: 10.1128/iai.72.12.7030-7039.2004
|View full text |Cite
|
Sign up to set email alerts
|

First-Time Isolation and Characterization of a Bacteriophage Encoding the Shiga Toxin 2c Variant, Which Is Globally Spread in Strains of Escherichia coli O157

Abstract: A bacteriophage encoding the Shiga toxin 2c variant (Stx2c) was isolated from the human Escherichia coli O157 strain CB2851 and shown to form lysogens on the E. coli K-12 laboratory strains C600 and MG1655. Production of Stx2c was found in the wild-type E. coli O157 strain and the K-12 lysogens and was inducible by growing bacteria in the presence of ciprofloxacin. Phage 2851 is the first reported viable bacteriophage which carries an stx 2c gene. Electron micrographs of phage 2851 showed particles with elonga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
(71 reference statements)
1
31
0
1
Order By: Relevance
“…It differs from the prototypical Stx2a-encoding phages BP-933W in its chromosomal integration site, phage morphology, and superinfection immunity (43,44). The Stx2c prophage found in lineage I/II strains (i.e., EC4115) have gene content and architecture similar to phage 2851 (23).…”
Section: Discussionmentioning
confidence: 99%
“…It differs from the prototypical Stx2a-encoding phages BP-933W in its chromosomal integration site, phage morphology, and superinfection immunity (43,44). The Stx2c prophage found in lineage I/II strains (i.e., EC4115) have gene content and architecture similar to phage 2851 (23).…”
Section: Discussionmentioning
confidence: 99%
“…Multiplex PCR was used to detect stx2c and the Stx2c-phage o and q genes (39) in 519 strains; stx data were missing for 19 strains, four of which were repeatedly stx-negative. The malate dehydrogenase (mdh) gene was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…5). Interestingly, the Sakai and EDL-933 genomes are more similar to each other in gene content and nucleotide sequence identity than to the clade 8 spinach outbreak strain, which carries additional genetic material including stx2c and the Stx2c lysogenic bacteriophage 2851 (39). This suggests that the spinach outbreak genome and, by inference, clade 8, has substantial time to diverge with respect to its genetic composition when compared with strains from other lineages.…”
Section: Figmentioning
confidence: 99%
“…Primers developed by Lin et al (30) give in the case of the stx 2c allele a product of 903 bp, which can be distinguished from the stx 2 gene by a HincII digestion. Such PCR-restriction fragment length polymorphism (RFLP) investigations revealed that stx 1 and stx 2c as well as stx 2 and stx 2c are frequently associated in O157:H7 and strains encoding only Stx2c are more rarely isolated (6,48,52). While Stx1 and Stx2 are disseminated over a large variety of STEC serotypes, the Stx2c type was found to be restricted mostly to STEC serotype O157:H7 and, moreover, to certain clonal lineages of that serotype (54); however, the reasons for this finding are not known.…”
mentioning
confidence: 99%